Students’ Perception of Lecturer Description in English Lecture Class at Stikes Bina Sehat PPNI Mojokerto, East Java. - ASEF WILDAN MUNFADLILA (English Education, Linguistics, and Literature Journal, 2022)
Students’ perception is how the students believe with what they feel throygh the sense tools that they have when they observe to lecturer talk during English class. This research aimed to examine the types of lecturer’s talk, to answer this issue of students in English class. the study applied a qualitative approach by observing classroom activities and administering the questionnaire to 40 student’s university student. The result indicated that the lecturer used questioning, giving feedback, negotiating, and giving instruction and information. There were three types of lecturer talk such as questioning, giving feedback, giving instruction and information. Negative perception was negotiating between lecturer and students. The result of this research implied that the lecturer needs to understand the way they talk when the lecturer able to talk effectively it will help the students understand the material well.